The Role of School Principals in Improving the Performance of School Administration Staff in Facing Society 5.0 - Imani, Hanna Nurul; Sunarni, Sunarni (Proceedings Series of Educational Studies, 2024)
Global development from the 4.0 era to Society 5.0 requires an increase in the competence of human resources in using technology. The researcher intends to be able to trace the leadership role that the principal has in preparing the competencies of School Administration Staff according to the times to be able to improve their performance. This study uses qualitative research on literature studies whose data sources are in the form of articles, books, and relevant documents and then records and reviews the results of the data collection. The results of the study state that the leadership role of the principal has a function that is not only limited to the leader but also the manager. In implementing change, the principal must be visionary to bring organizational success by formulating the right strategy to improve School Administration Staff performance by taking advantage of opportunities arising from global changes.